Factores de riesgos asociados a lesiones de ligamento cruzado anterior en pacientes del Consultorio de Rehabilitación Física “Hugo y Rosario”, parroquia san juan, periodo octubre 2024 – marzo 2025. - Cabero Cotto, Xiomara Katiusca (2025)
Anterior cruciate ligament (ACL) injuries are frequently present in the field of physiotherapy and sports medicine due to their impact on knee stability. Worldwide, there is a high incidence of these injuries. In Ecuador, although epidemiological information is scarce and not precise, it is known that these injuries constitute 50% of cases and in the San Juan parish there are several cases of the same. The main problem of the research topic is What are the risk factors associated with anterior cruciate ligament injuries in patients of the physical rehabilitation office "Hugo y Rosario, San Juan parish, period October 2024 - March 2025?", with the aim of solving this question, we seek to carry out a field study to obtain truthful and specific information on the subject through questionnaires and interviews that facilitate our analysis and satisfactory results, in this way the answers and solutions to this problem will be obtained. This study is aimed at students and health professionals as a guide and advance in the knowledge of the ACL present in physical therapy and rehabilitation.